Trends in the rates of health-care providers' recommendation for HPV vaccine from 2012 to 2018: a multi-round cross-sectional analysis of the health information national trends survey - Joël Fokom Domgue; Robert K. Yu; Sanjay Shete (Taylor & Francis Group, 2021)
The 2012 report of the President's Cancer Panel highlighted the overriding contribution of missed clinical opportunities to suboptimal HPV vaccination coverage. Since then, it remains unknown whether the rates of provider recommendations for the HPV vaccine in the US population have increased. We conducted an analysis of four rounds of the Health Information National Trends Survey (HINTS), a household survey of civilian US residents aged 18 y or older. A total of 1,415 (2012), 1,476 (2014), 1,208 (2017), and 1,344 (2018) respondents to the HINTS survey who were either HPV vaccine-eligible or living with HPV vaccine-eligible individuals were included. Overall, the rates of providers' recommendations remained stagnated from 2012 to 2018 in all categories of the study population, except for non-Hispanic Blacks (NHBs), where this prevalence increased during the study period (AAPC = 16.4%, p < .001). In vaccine-eligible individuals (18-27 y), declining trends were noted overall (AAPC = −21.6%, p < .001), among NHWs (AAPC = −30.2%, p < .001) and urban dwellers (AAPC = −21.4%, p < .001). Among vaccine-ineligible respondents (˃27 y) living with vaccine-eligible individuals, trends in the prevalence of provider recommendations for HPV vaccine were stagnating overall (AAPC = 0.5%, p = .90), and increasing only among NHBs (AAPC = 13.9%, p < .001). Despite recent progress, our findings indicate variations of trends in provider recommendations for the HPV vaccine in the US adult population according to age, sex, race/ethnicity, and residence. To accelerate HPV vaccination uptake, immediate actions to enhance provider recommendation for HPV vaccine are needed.